Pharmacodynamic effects and relationships to plasma and oral fluid pharmacokinetics after intravenous cocaine administration. (1st June 2016) - Ellefsen, Kayla N.; Concheiro, Marta; Pirard, Sandrine; Gorelick, David A.; Huestis, Marilyn A.
Highlights: Oral fluid (OF) and plasma pharmacokinetics after intravenous cocaine are presented. Peak subjective effects occurred at observed peak cocaine plasma concentrations. Peak effects (for some measures) occurred prior to peak OF cocaine concentrations. Cocaine T max was significantly longer in OF (0.5 h) compared to plasma (0.017 h). Cocaine and BE OF confirmatory cutoffs can be selected to meet drug testing needs. Abstract: Background: No controlled cocaine administration data describe cocaine and metabolite disposition in oral fluid (OF) collected with commercially-available collection devices, OF-plasma ratios, and pharmacodynamic relationships with plasma and OF cocaine and metabolite concentrations. Methods: Eleven healthy, cocaine-using adults received 25 mg intravenous cocaine. Physiological and subjective effects (visual analogue scales), and plasma were collected one hour prior, and up to 21 h post-dose. OF was collected with the Quantisal™ device up to 69 h post-dose. Cocaine, benzoylecgonine (BE) and ecgonine methyl ester were quantified in plasma by liquid chromatography-tandem mass spectrometry; cocaine and BE were quantified in OF by two dimensional-gas chromatography-mass spectrometry. Results: Increases in heart rate, blood pressure and positive subjective effects occurred within the first 15 min, persisting up to 1 h ("Rush"), with clockwise hysteresis observed for plasma and OF concentrations and some subjective measures. Peak subjective effects ("Rush, " "Good drug effect" and "Bad drug effect") occurred prior to peak OF cocaine concentration, whereas observed peak plasma concentrations and subjective measures occurred simultaneously, most likely due to significantly earlier plasma T max compared to OF T max. T last was generally longer in OF (12.5 h cocaine; 33.0 h BE) than plasma (9.5 h cocaine; >21 h BE, cutoffs 1 μg/L); 8 and 10 μg/L OF cocaine confirmatory cutoffs yielded detection times similar to cocaine's impairing effects, suggesting usefulness for DUID testing. Conclusions: OF offers advantages as an alternative matrix to blood and plasma for identifying cocaine intake, defining pharmacokinetic parameters at different confirmation cutoffs, and aiding different drug testing programs to best achieve their monitoring goals.